Compositionally tuned magnetron co-sputtered PtxNi100-x alloy as a cathode catalyst for proton exchange membrane fuel cells - Khalakhan, Ivan; Supik, Lukáš; Vorokhta, Mykhailo; Yakovlev, Yurii; Dopita, Milan; Sandbeck, Daniel; Cherevko, Serhiy; Veltruská, Kateřina; Matolínová, Iva (Applied Surface Science, 2020)
In this study, PtxNi100-x (0 ≤ x ≤ 100) alloy catalysts were prepared using magnetron co-sputtering in order to reveal the correlation between their composition and catalytic properties as a cathode in proton exchange membrane fuel cells (PEMFCs). Fine power adjustment on magnetrons allowed to deposit alloys with precise composition and at the same time with identical thickness of 10 nm and similar morphologies. The powerful surface characterization techniques such as atomic force microscopy (AFM), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), X-ray diffraction (XRD), X-ray reflectivity (XRR) and X-ray photoelectron spectroscopy (XPS) were applied to thoroughly investigate the catalytic layers. The desired composition of the films was confirmed by EDX and XRD results. All deposited layers showed similar morphologies with vertical and horizontal roughness of 0.35 nm and 6 nm, respectively. XRD confirmed the alloy nature of the films with one crystalline phase of the fcc PtNi. The PtxNi100-x alloys showed significant enhancement of specific power (SP) comparing to the pure Pt in PEMFC. Particularly, the Pt25Ni75 sample exhibited the highest SP of 24 kW/g(Pt). This catalyst showed a 2- and almost 10-fold improvement in SP with respect to the Pt film and commercial nanopowder Pt catalyst, respectively.
CRIS-Team Scopus Importer:2020-02-07
Keywords: Bimetallic catalyst; Fuel cell; Magnetron sputtering; Pt-Ni; Thin film